A descriptive survey of the interior design and spatial organization of bedrooms in the UP centennial dormitory in relation to spatial and visual perceptions - Pabillore, Alessandra A.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Dilman, 2016)
The study examined the interior design and spatial organization of two selected bedrooms in the U.P. Centennial Dormitory and how these affected the spatial and visual perception of the student residents. It specifically focused on the interior design components like size, furniture, color scheme, lighting, decor & accessories, acoustics, and ventilation whereas the spatial organization focused on the privacy, and furniture layout of the bedroom. The study utilized a quantitative descriptive survey approach as well as a multi-method case study approach in understanding the perceptions of the student residents. Purposive sampling was employed in the study. The bedroom samples should be located in the U.P. Centennial Dormitory, one bedroom should belong to each phase of the dormitory, and the bedrooms should each accommodate a total of six (6) student residents. Random sampling was also used for the selection of respondents in the study. The criteria used for the sample was that the respondent must currently reside in the U.P. Centennial Dormitory. The study also demonstrated the results through the percentage frequency distribution. The study utilized observation, photo-documentation, and survey questionnaires that were answered by one hundred respondents residing in the U.P. Centennial Dormitory. The results of this study showed that there are major factors that influenced the visual and spatial perceptions of the student residents. The major factors that emerged were the size of the study area, size of the study table furniture and storage, lack of proper lighting, lack of proper ventilation, lack of privacy, and lack of sense of control over the furniture layout. The significance of this study is to spur awareness among interior designers and architects and to enhance their knowledge on dormitory design in relation to the spatial and visual perceptions of its users.
Submitted June 2016.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Dormitories -- Philippines -- Interior decoration